Generative presentation of the structure of nouns in contemporary Bulgarian (Philology, 2026)
The aim of the article on the base of the syntactic structure of the sentence is to verify if it possible to construct the graf of the structure of the words – nouns. The structure of the morphological graf includes the inflections, the suffixes, the roots and the prefixes.
Keywords: syntactic graph; morphological graph; inflections; suffixes; roots; prefixes